Mineralization of a superficially porous microsphere scaffold via plasma modification. Issue 6 (13th January 2017) - Hou, Jie; Zhang, Fen; Cheng, Delin; Shi, Xuetao; Cao, Xiaodong
Abstract : Novel porous mineralization layers were obtained on scaffolds. The plasma process could enhance the bonding force between apatite and the substrate surface. Abstract : Mineralization on bone repair devices is beneficial for osteoconductivity and thus osteogenesis. Surface chemistry modification by plasma treatment can significantly improve mineralization. In this study, superficially porous poly(lactide- co -glycolide)/hydroxyapatite (PLGA/HA) microsphere scaffolds (PH) were processed by oxygen and ammonia plasma followed by incubation in simulated body fluids (SBF) for mineralization. The effect of plasma treatment and incubation time on the features of the mineralization layer was investigated. The results showed that novel porous mineralization layers were obtained on the unmodified PH (As-grown), oxygen pretreated PH (OPH) and ammonia pretreated PH (NPH). The mechanical property and superficially porous structures of scaffolds changed little after plasma treatment. However, OPH produced the most significant apatite layer with an increasing roughness with mineralization time. In contrast, As-grown just had a smooth mineralization layer. Moreover, the mineralization layer on As-grown was easy to peel off compared with those on OPH and NPH, demonstrating that plasma treatment could enhance the bonding force between apatite and the substrate surface. The surface chemical analysis proved that the difference in outcome of mineralization was because plasma treatment introduced additional polar domains onto the scaffolds. This work provided a promising mineralization material system for bone repair application.